2012
DOI: 10.1007/bf03261990
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and Communication in Sub-Saharan Africa

Abstract: In this narrative review, a brief summary of theoretical approaches to risk perception is followed by an analysis of some of the special factors influencing risk perception and risk communication in sub-Saharan Africa. Examples of recent and emergent local medicines and vaccine controversies in several countries are given along with evidence and analysis of how they were managed. These demonstrate, among other things, the extent to which ethnic, religious and cultural issues influence popular perception, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The study found that complacency, high levels of illiteracy, multi-ethnic diversity, limited access to main and social media (especially in rural areas), a lack of alternatives (such as economic activities, water, food, scarcity of land), emotional attachment to place, limited access to experts who were perceived to be neutral, and lack of trust between locals and government officials were some of the main barriers to risk communication in the Niger Delta. These findings are similar to the study by Dodoo and Hugman (2012) who asserted that there is limited capacity for credible and reliable scientific assessment and public communication strategies in sub-Saharan Africa. In part, this reflects the relatively low levels of scientific literacy in the region and the power gradients that exist between local communities and the corporate–government nexus.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The study found that complacency, high levels of illiteracy, multi-ethnic diversity, limited access to main and social media (especially in rural areas), a lack of alternatives (such as economic activities, water, food, scarcity of land), emotional attachment to place, limited access to experts who were perceived to be neutral, and lack of trust between locals and government officials were some of the main barriers to risk communication in the Niger Delta. These findings are similar to the study by Dodoo and Hugman (2012) who asserted that there is limited capacity for credible and reliable scientific assessment and public communication strategies in sub-Saharan Africa. In part, this reflects the relatively low levels of scientific literacy in the region and the power gradients that exist between local communities and the corporate–government nexus.…”
Section: Resultssupporting
confidence: 89%
“…There have, however, been very few such studies and so the use of risk communication as a potential mitigation strategy is an area that needs further attention. Dodoo and Hugman (2012) identified several factors impeding effective risk communication in sub-Saharan Africa including limited ability to collect useful data, few credible and reliable scientific assessment practices, and few robust risk management and public communication strategies. When considering the role of the media in such situations, Edafienene (2012) found that the media had little or no influence on risk-related policy decisions in the Niger Delta.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are differences in levels of education, culture and living conditions amongst people in Ghana and other SSA countries compared to those living in Europe and other high-income countries. Such differences may lead to variations in knowledge and perception on medications, ADRs and ADR reporting [19, 20]. It is also of importance to know what motivates patients in Ghana to report an ADR and whether they know the formal channels for ADR reporting including direct patient reporting.…”
Section: Introductionmentioning
confidence: 99%
“…This barrier also exists when communicating with broader audiences, and Dodoo and Hugman[24] give us important advice in this respect: public concerns have to be addressed, whether or not, as pharmacovigilance professionals, we share these concerns. The authors take us on a journey through sub-Saharan Africa, with examples illustrating how risk communication may be linked with social problems and citizens’ trust — or often mistrust — in governments.…”
mentioning
confidence: 99%